Terraforming and monumentality in hunter-gatherer-fisher societies: Towards a conceptual and analytical framework. Issue 1 (December 2017) - Grier, Colin; Schwadron, Margo
Abstract : Terraforming and monumentality have been integral to the practices of many hunter-gatherer-fisher (HGF) societies around the world. Both mobile and sedentary HGFs were capable of producing large, planned mound complexes, expansive production and defensive features, and other types of landscape modifications. We present a framework for approaching these practices, in an attempt to break down lingering conceptual barriers in the way HGFs have been viewed archaeologically and anthropologically, particularly in their relationship to landscapes. We offer operational definitions for key terms, including terraforming, monumental construction, monument, and monumentality, which constitute core concepts in addressing HGF monumentality.